2020
DOI: 10.1002/ente.201901360
|View full text |Cite
|
Sign up to set email alerts
|

Passive Direct Methanol–Hydrogen Peroxide Fuel Cell with Reduced Graphene Oxide–Supported Prussian Blue as Catalyst

Abstract: Herein, a reduced graphene oxide–supported Prussian Blue (rGO‐PB) composite as the cathode catalyst for a passive direct methanol–hydrogen peroxide fuel cell (DMHPFC) is used. Unlike the conventional passive direct methanol fuel cell (DMFC) with a cathodic catalyst of noble metal platinum (Pt), the new fuel cell uses hydrogen peroxide as the oxidant. This nonnoble metal catalyst has a low cost, high catalytic activity, and high conductivity due to its 3D conductive network. The fuel cell has a theoretical volt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 53 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…[241] The advances in catalyst technology have led to more efficient and durable FCs that can operate at higher temperatures, reducing the need for expensive cooling systems. [242] Additionally, catalysts are vital components in FCs, as they facilitate the electrochemical reactions. [243] Currently, most FC catalysts use platinum or other precious metals, which are costly and limited in supply.…”
Section: Future Outlook Of Fuel Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…[241] The advances in catalyst technology have led to more efficient and durable FCs that can operate at higher temperatures, reducing the need for expensive cooling systems. [242] Additionally, catalysts are vital components in FCs, as they facilitate the electrochemical reactions. [243] Currently, most FC catalysts use platinum or other precious metals, which are costly and limited in supply.…”
Section: Future Outlook Of Fuel Cellsmentioning
confidence: 99%
“…In case of FC, the catalyst's role is to accelerate the reactions which occur when hydrogen and oxygen are combined to produce electricity [241] . The advances in catalyst technology have led to more efficient and durable FCs that can operate at higher temperatures, reducing the need for expensive cooling systems [242] . Additionally, catalysts are vital components in FCs, as they facilitate the electrochemical reactions [243] .…”
Section: Future Outlook Of Fuel Cellsmentioning
confidence: 99%
“…Nevertheless, according to the authors, in general, the PDs obtained in this study were higher than those described in the literature. Another less disruptive approach can be found in the work reported by Lu et al [177], which studied a passive DMFC using H 2 O 2 as the oxidant, i.e., a passive direct methanol-hydrogen peroxide fuel cell (DMHPFC). This fuel cell had a theoretical voltage of 1.76 V (higher than 1.21 V for the traditional DMFC) and could be used in an oxygen-free environment.…”
Section: Alternative Oxidantsmentioning
confidence: 99%
“…[9,10] The structural parameters include the physical parameters of the membrane electrode assembly (MEA) and the geometric parameters of the flow field structure. [11][12][13] Studies showed that optimizing the operating parameters and the cell structure are two effective ways to enhance DMFC performance. [14][15][16][17] Yang et al [18] developed a serpent flow fields structure for DMFC, and the results showed that with this structure, the DMFCs delivered better performance under various conditions.…”
mentioning
confidence: 99%